2007
DOI: 10.3324/haematol.10531
|View full text |Cite
|
Sign up to set email alerts
|

High loading dose AmBisome(R) is efficacious and well tolerated in the management of invasive fungal infection in hematology patients

Abstract: High loading dose AmBisome® is efficacious and well tolerated in the management of invasive fungal infection in hematology patientsDespite improved supportive care, and the introduction of less toxic lipid-formulations of amphotericin B deoxycholate and other new antifungal agents the mortality from invasive fungal infection (IFI) in hematology patients remains high. New management strategies are therefore required to improve outcome. Haematologica 2007; 92: 92:572-573

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…If choosing to employ high-dose therapy, clinicians should follow best practices to monitor kidney function and changes in electrolytes daily whilst on amphotericin B therapy. Although response and mortality rates in our case series were consistent with previously reported literature, [14][15][16][17][18][19][20][21][22][23][24] the range of favourable responses in multi-patient studies (8-68%) is still dismally low.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…If choosing to employ high-dose therapy, clinicians should follow best practices to monitor kidney function and changes in electrolytes daily whilst on amphotericin B therapy. Although response and mortality rates in our case series were consistent with previously reported literature, [14][15][16][17][18][19][20][21][22][23][24] the range of favourable responses in multi-patient studies (8-68%) is still dismally low.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 11 manuscripts met inclusion criteria and were included in this review (Table 2). [14][15][16][17][18][19][20][21][22][23][24] Of these, seven were case reports or case series, one was a retrospective evaluation, and three were prospective studies (1 pilot, one open label, one randomized controlled trial). A total of 260 patients, ranging from 8 to 69 years of age, were represented in the published literature.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…They reported that a 15 mg/kg/day dose was well tolerated and can effectively treat aspergillosis and other filamentous fungal infections [76]. Lorna et al also concluded that a high dose of LAmB (10 mg/kg/day) efficacious and well tolerated in treating IFD in haematology patients [77]. These significant clinical findings have led to the largest AMBITION-cm global trial for HIV-associated cryptococcal meningitis patients in low-resource countries.…”
Section: Amphotericin Bmentioning
confidence: 99%